Barriers or boosters? the role of governance pathways in deploying offshore carbon capture and storage: comparative implications from the EU and China - Wang, Jinpeng; Zhang, Meng (Frontiers in Marine Science, 2025)
Offshore carbon capture and storage (CCS) deployment has been hailed as a game changer in the ever-changing climate game in the era of Paris Agreement. In the European Union (EU), rigorous regulation within a legal framework governs cross-border offshore CCS projects, while China adopts a flexible policy-oriented approach. This article employs a multi-method research approach, combining legal doctrinal analysis, comparative studies, and discourse analysis, to examine the role of governance tools in offshore CCS deployment in the EU and China, highlighting their differing models and the implications for effective governance. The discrepancies in governance models for offshore CCS deployment between the EU and China arise from variations in legal traditions, disparities in the legal status of marine areas hosting offshore CCS projects, and differences in involved industries. The paradox between normative governance and offshore CCS deployment finds resonance and explanation in the “Collingridge Dilemma”. Experiences from both the EU and China underscore the significance of a tailored-made and well-balanced governance portfolio of legal and policy tools in regulating and facilitating offshore CCS deployment. Policy and law should act hands in hands as twin engines in a sound governance framework propelling the momentum of offshore CCS deployment forward.